Retrospective study of 14 cases of canine arthritis secondary to Leishmania infection. (3rd April 2014) - Sbrana, S.; Marchetti, V.; Mancianti, F.; Guidi, G.; Bennett, D.
<x xml:space="preserve">Abstract</x> OBJECTIVE To describe the clinical appearance, laboratory findings and response to treatment of dogs with inflammatory joint disease associated with Leishmania infection. METHODS Retrospective analysis of case records of dogs with serologically confirmed leishmaniasis and concurrent inflammatory joint disease presented between 2005 and 2011. RESULTS In total, 14 cases met the inclusion criteria. Of these, five (36%) dogs were presented with monoarthritis, five (36%) with oligoarthritis and four (28%) with polyarthritis. The most frequently affected joint was the carpus. Both erosive and non‐erosive disease was identified on radiographic examination. All dogs had an inflammatory synovial fluid with a high white cell count and a preponderance of neutrophils, and in eight (57%) cases Leishmania amastigotes were found in the synovial fluid smears. Dogs were treated with 50 mg/kg N‐methylglucamine antimoniate twice a day for 1 month and 10 mg/kg allopurinol twice a day for 6 to 9 months combined with prednisolone in five cases. At the 6‐month follow‐up, eight (57%) dogs showed improvement in general and orthopaedic signs and four (28%) dogs were stable. CLINICAL SIGNIFICANCE Leishmaniasis should be considered a differential diagnosis in dogs with inflammatory arthritis in endemic areas.